Examining fifty cases of convicted online romance fraud offenders - Soares, Adebayo Benedict (Criminal justice studies, 2024)
This article examines fifty case files of cybercriminals that the Economic and Financial Crimes Commission (EFCC) convicted for online romance fraud. It profiles offenders and explores the value of the Space Transition Theory in understanding digital crimes. Through documentary analysis, the study identifies key patterns in victim demographics, fraudsters’ operational strategies, and offenders’ socioeconomic backgrounds. Findings reveal a high concentration of U.S. victims (56%) and a preference among offenders for Apple’s iPhone (58%). Most offenders presented themselves as Caucasian American males (46%) or military personnel (12%), with some adopting Caucasian European male identities (10%). Victim demographics show a pronounced gender disparity: 70% of offenders primarily targeted female victims, 14% targeted male victims, 10% reached both genders, and 6% did not specify the victims’ gender. The analysis also indicates that most offenders were university students (74%), with Facebook (46%) identified as the primary platform for these fraudulent activities. The study emphasizes the need for prevention strategies that genuinely consider the socioeconomic and political conditions that may make online fraud an appealing career option.